2015
DOI: 10.1039/c5em00240k
|View full text |Cite
|
Sign up to set email alerts
|

Comparative adsorption of Eu(iii) and Am(iii) on TPD

Abstract: Comparative adsorption behaviors of Eu(III) and Am(III) on thorium phosphate diphosphate (TPD), i.e., Th4(PO4)4P2O7, have been studied using a batch approach and surface complexation model (SCM) in this study. The results showed that Eu(III) and Am(III) adsorption increased to a large extent with the increase in TPD dose. Strong pH-dependence was observed in both Eu(III) and Am(III) adsorption processes, suggesting that inner-sphere complexes (ISCs) were possibly responsible for the adsorption of Eu(III) and A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
(58 reference statements)
0
2
0
Order By: Relevance
“…Ni(II) sorption decreased with the increase in ionic strength below pH 8.0. This suggested that IE or OSCs were dominant mechanisms in the low pH range because both are very sensitive to the ionic strength 36 . No significant difference was observed at different ionic strength conditions above pH 8.0.…”
Section: Resultsmentioning
confidence: 99%
“…Ni(II) sorption decreased with the increase in ionic strength below pH 8.0. This suggested that IE or OSCs were dominant mechanisms in the low pH range because both are very sensitive to the ionic strength 36 . No significant difference was observed at different ionic strength conditions above pH 8.0.…”
Section: Resultsmentioning
confidence: 99%
“…Europium(III), i.e., Eu(III), is commonly considered as a chemical analogue for trivalent lanthanides (Ln) and actinides (An) due to the similar electronic and bonding properties (Takahashi et al, 1998a;Bradbury et al, 2002;Stumpf et al, 2002;Pan et al, 2017). As such, the retention of Eu(III) on various potential barriers has been extensively investigated to provide fundamental data concerning the performance assessment of HLW repositories and the remediation of radioactive contaminations (Fan et al, 2015; J o u r n a l P r e -p r o o f Fukushi et al, 2013;Jin et al, 2014;Pan et al, 2017;Qiu et al, 2018). It was reported that pH, ionic strength and NOMs largely influenced Eu(III) adsorption on muscovite, bentonite, illite, montmorillonite, granite, soil, etc.…”
Section: Introductionmentioning
confidence: 99%